The Tyranny of the Everyday in Mobile Video Messaging - Rintel, Sean; Harper, Richard; O'Hara, Kenton (CHI 2016, 2016)
This paper reports on how asynchronous mobile video messaging presents users with a challenge to doing ‘being ordinary’. 53 participants from three countries were recruited to try Skype Qik at launch for two weeks. Some participants embraced Skype Qik as a gift economy, emphasizing a special relationship enacted through crafted self-presentation. However, gift exchange makes up only a small proportion of conversation. Many participants struggled with the self-presentation obligations of video when attempting more everyday conversation. Faced with the ‘tyranny of the everyday’, many participants reverted to other systems where content forms reflected more lightweight exchange. We argue that designing for fluid control of the obligations of turn exchange is key to mobile applications intended to support everyday messaging.